A Philosophical Embodied Practice: Meditation in the European–Italian Adult Education Context. Issue 161 (5th March 2019) - Formenti, Laura
Abstract: This chapter describes a practice of philosophical meditation as a way to transformation in an Italian context. It makes use of poetic and autoethnographic writing to highlight some features of the method, and offers suggestion for adult education practice.